A novel hybrid image authentication scheme based on absolute moment block truncation coding - Lin, Chia-Chen; Huang, Yuehong; Tai, Wei-Liang (My University, 2017)
We propose a novel hybrid image authentication scheme to protect the integrity of images compressed by absolute moment block truncation coding (AMBTC). In this paper, we use a hybrid strategy to embed the authentication codes using AMBTC that at the same time improves the embedding efficiency. All blocks of a compressed image are classified into two groups, smooth and complex, which have different characteristics and may suit different embedding methods. For smooth blocks, the authentication code will be embedded into the bitmap (BM) of each block. For complex blocks, the authentication code will be embedded into quantization levels of each block according to a reference table. In contrast to the previous approach, the hybrid strategy allows for a high utilization of blocks that have high embedding efficiency for embedding, thus giving a significantly improved embedding capacity than the previous approach. The performance is evaluated experimentally to demonstrate that our proposed scheme provides improved image quality and is less vulnerable to tampering compared with existing methods.
Keywords: Image authentication; Tamper detection; Absolute moment block truncation coding; Watermarking